2015
DOI: 10.3389/fendo.2015.00167
|View full text |Cite
|
Sign up to set email alerts
|

A Broad G Protein-Coupled Receptor Internalization Assay that Combines SNAP-Tag Labeling, Diffusion-Enhanced Resonance Energy Transfer, and a Highly Emissive Terbium Cryptate

Abstract: Although G protein-coupled receptor (GPCR) internalization has long been considered as a major aspect of the desensitization process that tunes ligand responsiveness, internalization is also involved in receptor resensitization and signaling, as well as the ligand scavenging function of some atypical receptors. Internalization thus contributes to the diversity of GPCR-dependent signaling, and its dynamics and quantification in living cells has generated considerable interest. We developed a robust and sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 57 publications
(67 reference statements)
3
62
0
Order By: Relevance
“…The results of our study showed reduced internalization at 500 nM CYTL1 compared with 50 nM CYTL1. Reportedly, there was also reduced internalization extent at a higher concentration of ligand in other studies related with receptor internalization assays (36), which was similar with our results. In our study, it might be due to the fact that CYTL1 at high concentrations induced obvious receptor internalization at different time points and we detected robust internalization extent induced by 50 nM CYTL1 and modest internalization extent induced by 500 nM in 15 min.…”
Section: Discussionsupporting
confidence: 93%
“…The results of our study showed reduced internalization at 500 nM CYTL1 compared with 50 nM CYTL1. Reportedly, there was also reduced internalization extent at a higher concentration of ligand in other studies related with receptor internalization assays (36), which was similar with our results. In our study, it might be due to the fact that CYTL1 at high concentrations induced obvious receptor internalization at different time points and we detected robust internalization extent induced by 50 nM CYTL1 and modest internalization extent induced by 500 nM in 15 min.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we show that an experimental setup in which labeling is performed at 4°C successfully detects constitutive internalization of GPRC6A. This is in agreement with Levoye et al (38) in which constitutive internalization of the CXC chemokine receptor 7 was detected by means of the real-time internalization assay using 4°C labeling.…”
Section: Discussionsupporting
confidence: 93%
“…The assay allows for detection of receptor internalization in a time-dependent manner and is performed in a 96-well format, thus enabling higher throughput than previously available methods. To verify the real-time internalization technique, two groups tested a range of GPCRs and correlated results from the realtime assay with classical immunocytochemistry experiments (37,38). Moreover, GLP1R internalization was tested in the presence of a dominant-negative mutant of dynamin, which blocks dynamin-dependent internalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5.9, 5.12, and 6.3 of Stoddart et al (44)]. The intracellular FFAR2/3 fraction may be due to constitutive internalization of agonist-free GPCR, which has been observed for a subset of GPCRs, such as the putative nutrient sensing receptor GPRC6A (48) and the atypical chemokine receptor 3 (49). Confirming this will require further studies.…”
Section: Resultsmentioning
confidence: 98%